Desynchronization of autonomic response and central autonomic network connectivity in posttraumatic stress disorder - Thome, Janine; Koenig, Julian (Human brain mapping, 2017)
Objectives: Although dysfunctional emotion regulatory capacities are increasingly recognized as contributing to posttraumatic stress disorder (PTSD), little work has sought to identify biological markers of this vulnerability. Heart rate variability (HRV) is a promising biomarker that, together with neuroimaging, may assist in gaining a deeper understanding of emotion dysregulation in PTSD. The objective of the present study was, therefore, to characterize autonomic response patterns, and their related neuronal patterns in individuals with PTSD at rest. Methods: PTSD patients (N = 57) and healthy controls (N = 41) underwent resting‐state fMRI. Connectivity patterns of key regions within the central autonomic network (CAN)—including the ventromedial prefrontal cortex (vmPFC), amygdala, and periaqueductal gray (PAG)—were examined using a seed‐based approach. Observed connectivity patterns were then correlated to resting HRV. Results: In contrast to controls, individuals with PTSD exhibited lower HRV. In addition, whereas controls engaged a localized connectivity pattern of CAN‐related brain regions, in PTSD, key CAN regions were associated with widespread connectivity patterns in regions related to emotional reactivity (vmPFC and amygdala to insular cortex and lentiform nucleus; PAG to insula) and motor readiness (vmPFC and amygdala to precentral gyrus; PAG to precentral gyrus and cerebellum). Critically, whereas CAN connectivity in controls was strongly related to higher HRV (insula, mPFC, superior frontal cortex, thalamus), HRV covariation was absent in PTSD subjects. Conclusions: This study provides the first evidence for a specific psychophysiological–neuronal profile in PTSD individuals characterized by lower resting HRV and a lack of HRV covariation with CAN‐related brain connectivity.
Published online: 20 September 2016
Gesehen am 04.04.2018